Let's talk about aging parents : a real-life guide to solving problems with 27 essential conversations - Tamblyn Watts, Laura (The Experiment, 2024)
"Caring for an older relative can be complicated, but this book of conversational scripts and expert advice will help you do the right thing and put your anxieties to rest"--